Pengaruh Variabel Internal Bank Terhadap Penyaluran Kredit Emiten Bank Umum Konvensional BUKU 4 - Batara M. Simatupang (STIE Indonesia Banking School, 2023)
This study analyzed the impact of bank’s internal factors: Third Party Funds (TPF), CAR, LDR, NPL and loan interest rate towards loan distributions on BUKU 4 commercial banks that listed in Bursa Efek Indonesia (BEI) during 2016 – 2020. The population on this research consists of all the BUKU 4 commercial banks that are issuer at BEI. Purposive sampling method are used with panel data analysis and the samples are Bank BRI, Bank Mandiri, Bank BNI and Bank BCA. The result that will be obtained from this research are for discovering bank’s internal variable that affected loan distributions on BUKU 4 commercial banks.